119k views
1 vote
−2a−9=6a+15 . Check your solution.

2 Answers

7 votes

Answer:

−2a−9 = 6a+15

-2a-6a = 15+9

-8a = 24

a = -3

Checking:

-2·(-3) - 9 = 6·(-3) + 15

6 -9 = -18 +15

-3 = -3

User Tomika
by
5.0k points
5 votes

Answer:

a = -3

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

-2a - 9 = 6a + 15

Step 2: Solve for a

  1. Add 2a on both sides: -9 = 8a + 15
  2. Subtract 15 on both sides: -24 = 8a
  3. Divide 8 on both sides: -3 = a
  4. Rewrite: a = -3

Step 3: Check

Plug in a into the original equation to verify it is a solution.

  1. Substitute in a: -2(-3) - 9 = 6(-3) + 15
  2. Multiply: 6 - 9 = -18 + 15
  3. Subtract/Add: -3 = -3

Here we see that -3 does indeed equal -3.

∴ a = -3 is a solution of the equation.

User Utpal
by
5.1k points